An assisted navigation method for telepresence robots - Meléndez-Fernández, Francisco; Galindo-Andrades, Cipriano; González-Jiménez, Antonio Javier (My University, 2016)
Telepresence robots have emerged as a new means of interaction in remote environments. However, the use of such robots is still limited due to safety and usability issues when operating in human-like environments. This work addresses these issues by enhancing the robot navigation through a collaborative control method that assists the user to negotiate obstacles. The method has been implemented in a commercial telepresence robot and a user study has been conducted in order to test the suitability of our approach.
Keywords: Robots autónomos